2009
DOI: 10.1021/la9032805
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Surface Energy and Wetability with Diels−Alder Chemistry

Abstract: Reversible Diels-Alder chemistry was utilized to manipulate the surface energy of glass substrates. Hydrophobic dieneophiles were prepared and attached to glass slides and capillaries to yield a nonwetting surface. Thermal treatment of the surfaces cleaved the Diels-Alder linkage, and resulted in the fabrication of a hydrophilic surface. Preliminary analysis utilized contact angle (CA) measurements to monitor the change in surface energy, and observed a hydrophilic state (CA - 70 +/- 3 degrees) before attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
1
29
0
1
Order By: Relevance
“…More recently reversible Diels-Alder chemistry has been used to manipulate surface wettability of the silanized glass surfaces. 163 The relationship between the rate of an interfacial Diels-Alder reaction and the steric congestion around the reacting molecules has been studied in detail. 164 It was found that for monolayers presenting quinone groups (the dienophile) in an accessible environment, i.e.…”
Section: Diels-alder Reactionsmentioning
confidence: 99%
“…More recently reversible Diels-Alder chemistry has been used to manipulate surface wettability of the silanized glass surfaces. 163 The relationship between the rate of an interfacial Diels-Alder reaction and the steric congestion around the reacting molecules has been studied in detail. 164 It was found that for monolayers presenting quinone groups (the dienophile) in an accessible environment, i.e.…”
Section: Diels-alder Reactionsmentioning
confidence: 99%
“…Other applications in the field of material science motivated the use of interfacial DA reactions from diene‐ or dienophile‐terminated silane assemblies. For instance, fluorinated compounds could be selectively immobilized by a DA reaction to control the wettability of the glass substrates . Fullerenes were grafted onto silicon wafers through DA reaction between C 60 and anthracene‐terminated monolayers to engineer transistors or sensors.…”
Section: Design Of Surfaces Able To React Via Interfacial Diels–aldermentioning
confidence: 99%
“…For instance, fluorinated compounds could be selectively immobilized by a DA reaction to control the wettability of the glass substrates. [114] Fullerenes were grafted onto silicon wafers through DA reaction between C 60 and anthracene-terminated monolayers [115] to engineer transistors or sensors. For applications in the field of nanocomposites, silica nanoparticles (often used as crosslinkers) were functionalized with maleimide groups and their reactivity with furan investigated.…”
Section: Interfacial Diels-alder Reaction On Monolayers or Silane Assmentioning
confidence: 99%
See 1 more Smart Citation
“…Deux approches ontétéélaborées : la première repose sur le greffage de polymères parfaitement définis intégrant en extrémité de chaîne un motif catéchol et la seconde approche consisteà fonctionnaliser préalablement la surfaceà l'aide d'une ancre spécifique comportant d'une part le motif catéchol et d'autre part une entité susceptible de réagir avec une entité complémentaire dans le cadre d'une réaction réversible de cycloaddition de type Diels Alder [6].…”
Section: Introductionunclassified